Vasculite cutânea induzida por propiltiouracil - Milanez, Fernanda Manente (2008)
The use of propylthiouracil (PTU) is associated with the development of different auto-antibodies, amongst them are antineutrophil cytoplasmic antibodies (ANCA) that are involved in the pathogenesis of ANCA associated systemic vasculitis. The case of a 46-years old woman who presented cutaneous vasculitis when taking PTU for Graves' disease is reported. Perinuclear ANCA (p-ANCA) was positive with titer > 1/320, but anti-myeloperoxidase antibodies were not detected. Skin biopsy showed leucocytoclastic vasculitis. The patient improved within ten days after withdrawing PTU and the resolution of hyperthyroidism was achieved with radioiodine (131I). The p-ANCA test remained positive > 1/320 eight months and four years after PTU withdrawal.